2024
DOI: 10.1002/anie.202320076
|View full text |Cite
|
Sign up to set email alerts
|

π‐Extended Diaza[7]helicenes with Dual Negatively Curved Heptagons: Extensive Synthesis and Spontaneous Resolution into Strippable Homochiral Lamellae with Helical Symmetry

Fuwei Gan,
Guoli Zhang,
Juncong Liang
et al.

Abstract: We report a unique category of π‐extended diaza[7]helicenes with double negative curvatures. This is achieved by two‐fold regioselective heptagonal cyclization of the oligoarylene‐carbazole precursors through either intramolecular C‐H arylation or Scholl reaction. The fusion of two heptagonal rings in the helical skeleton dramatically increases the intramolecular strain and forces the two terminal carbazole moieties to stack in a compressed fashion. The presence of the deformable negatively curved heptagonal r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…Recently, Qiu and co-workers revealed that πextended diaza [7]helicenes with two heptagons showed structure-dependent stacking switching from heterochiral packing to intralayer homochiral stacking. 44 Despite these recent advances in accessing negatively curved aromatics with helical subunits, both their negative curvature and helicity cause a very challenging synthesis, and longer [n]helicenecontaining nanographenes (n > 6), especially those containing heteroatoms, remain largely unexplored. Cyclopenta[ef ]heptalene (CPH), which is also known as aceheptylene, is a typical joint pentagon-heptagon-heptagon (5−7−7) nonalternant hydrocarbon that was initially studied by Hoffmann in 1959, 45−47 and its N-centered analog has not been reported to date (Figure 1b).…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Qiu and co-workers revealed that πextended diaza [7]helicenes with two heptagons showed structure-dependent stacking switching from heterochiral packing to intralayer homochiral stacking. 44 Despite these recent advances in accessing negatively curved aromatics with helical subunits, both their negative curvature and helicity cause a very challenging synthesis, and longer [n]helicenecontaining nanographenes (n > 6), especially those containing heteroatoms, remain largely unexplored. Cyclopenta[ef ]heptalene (CPH), which is also known as aceheptylene, is a typical joint pentagon-heptagon-heptagon (5−7−7) nonalternant hydrocarbon that was initially studied by Hoffmann in 1959, 45−47 and its N-centered analog has not been reported to date (Figure 1b).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Similarly, many negatively curved nanographenes containing [5]­helicenes have also been developed via regioselective cyclodehydrogenations. In addition, a series of large helical nanographenes embedded with tropone units exhibited intriguing optical properties, such as outstanding fluorescence quantum yield, good chiroptical response, and two-photon absorption. , Heteroatom doping is a common approach to enrich these molecular systems and results in desirable properties, including enhanced emissions, redox behaviors and highly ordered molecular arrangements. To date, only limited examples incorporating both the nonalternant topologies and heteroatoms have been explored. For instance, Ishigaki et al and our group independently reported highly twisted N-doped heptalene derivatives (Figure a), which showed high racemization barriers, reversible oxidation, and stable enantiopure cation species with near-infrared region absorption after chemical oxidation. Recently, Qiu and co-workers revealed that π-extended diaza[7]­helicenes with two heptagons showed structure-dependent stacking switching from heterochiral packing to intralayer homochiral stacking . Despite these recent advances in accessing negatively curved aromatics with helical subunits, both their negative curvature and helicity cause a very challenging synthesis, and longer [n]­helicene-containing nanographenes ( n > 6), especially those containing heteroatoms, remain largely unexplored.…”
Section: Introductionmentioning
confidence: 99%